PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA TENAGA KONTRAK DI RUMAH SAKIT ALOEI SABOE KOTA GORONTALO - Irwan Yantu; Agus Hakri Bokingo; Moh. Rizal D. Pade (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to determine the effect of job satisfaction on the turnover intentions of contract workers at Aloe Saboe Hospital in Gorontalo City. The method used in this study is a quantitative method. The data collection methodology for this study used a questionnaire with a specific sample of 36 respondents using a sampling technique using purposive sampling methods. Data were analyzed using simple regression analysis. The results of the study show that the statistical hypothesis meets the criteria that H0 is rejected and Ha is accepted, or that job satisfaction positively influences the intention to leave.